Mycobacterial contamination of fibreoptic bronchoscopes. Issue 12 (December 1993) - Brown, N M; Hellyar, E A; Harvey, J E; Reeves, D S
Abstract : Contamination of bronchoalveolar lavage specimens by environmental mycobacteria in hospital water supplies may lead to diagnostic confusion, particularly in immunocompromised patients. Mycobacteria may become concentrated in the tubing of bronchoscope disinfecting machines. It is very difficult to eradicate these organisms once contamination has occurred.